Piezoelectricity in non-nitride III–V nanowires: Challenges and opportunities. Issue 6 (27th February 2018) - Calahorra, Yonatan; Kar-Narayan, Sohini
Abstract: Abstract : The increasing demand for portable and low-power electronics for applications in self-powered devices and sensors has spurred interest in the development of efficient piezoelectric materials, via which mechanical energy from ambient vibrations can be transformed into electrical energy for autonomous devices, or which can be used in strain-sensitive applications. Semiconducting piezoelectric materials are ideal candidates in the emerging field of piezotronics and piezophototronics, where the development of a piezopotential in response to stress/strain can be used to tune the band structure of the semiconductor and hence its electronic and/or optical properties. Furthermore, research into nanowires of these materials has intensified due to the enhancement of piezoelectric properties at the nanoscale. In this regard, nanowires of ZnO and the III-nitrides have been extensively studied, but the piezoelectric properties of non-nitride III–V semiconductor nanowires remain less-explored. Indeed, direct measurements of the piezoelectric properties of single III–V nanowires are tellingly rare due to the difficulties associated with measurements of piezoelectric properties of nanoscale objects using conventional scanning probe microscopy techniques. This review addresses the challenges related to the study of piezoelectricity in III–V nanowires and the opportunities that lie therein in terms of device applications.